Influence of fulvic acid in feed additives on protein change and dairy productivity of cows - A. V. Kuzmenkova (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2021)
The main task of animal husbandry is to obtain large volumes of products: increasing the weight gain of cows and milk yields in a short time at minimal cost. The existing feeding standards for cattle are based on the use of Class 1 feed. In farms, most feed contains a low concentration of nutrients, the feeding of which does not allow to maintain the standard ratio of the diet. The quality of milk is not only of economic importance, which determines the profitability and competitiveness of dairy products in the market, but also of social significance, which is associated with the impact on human health. The most important factor determining the quality of milk and its suitability for further processing is the fullness of animal feeding: the energy value of the feed ration, the ratio of basic nutrients. The article presents data on the effect of the feed additive "Furor" based on fulvic acid, developed by LLC "Esson", which.